2022
DOI: 10.1096/fasebj.2022.36.s1.0r251
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐function relationships for the lncRNA SChLAP1 in aggressive prostate cancer

Abstract: Advances in deep sequencing technologies have facilitated the identification and annotation of thousands of long noncoding RNAs (lncRNAs) across the transcriptome. LncRNAs are documented to play critical housekeeping roles within the cell and are implicated in a wide variety of diseases, including cancer. While studies into lncRNA function in cancer abound, there are limited examples to date of detailed lncRNA structural analyses to enable understanding of structure‐function relationships. Understanding struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…LncRNA mediated mechanisms have been associated with epigenetic changes in prostate cancer. According to the results of the COSMIC-021, combination of the cabozantinib, a kind of antiangiogenic drugs, with the immune checkpoint inhibitor atezolizumab achieved encouraging activity in patients with metastatic castration-resistant PC (mCRPC), while multiple previous phase III clinical trials 5,6 in refractory CRPC have demonstrated increased toxicity with no clinical benefit. Tumor angiogenesis is regulated through interaction between anti-angiogenic factors and proangiogenic within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNA mediated mechanisms have been associated with epigenetic changes in prostate cancer. According to the results of the COSMIC-021, combination of the cabozantinib, a kind of antiangiogenic drugs, with the immune checkpoint inhibitor atezolizumab achieved encouraging activity in patients with metastatic castration-resistant PC (mCRPC), while multiple previous phase III clinical trials 5,6 in refractory CRPC have demonstrated increased toxicity with no clinical benefit. Tumor angiogenesis is regulated through interaction between anti-angiogenic factors and proangiogenic within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Progensa PCA3 test was successfully approved by the US Food and Drug Administration (FDA) in 2012 [ 5 ]. The lncRNA Second Chromosome Locus Associated with Prostate 1 (SChLAP1) has also been identified as a molecular driver and predictive biomarker of aggressive PCa in multiple clinical studies [ 6 ]. PCa is the foremost non-cutaneous malignancy in men worldwide, with increasing morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%